A glyphosate-based herbicide in a free-choice test on parasitism, emergence, and female-biased sex ratio of 10 Trichogrammatidae - Pontes, Jonas Pereira; Demolin Leite, Germano Leao; Rodrigues Bispo, Edilson Paulo; Tavares, Wagner de Souza; Guimaraes de Menezes, Claubert Wagner; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola (Springer, 2020)
Trichogrammatidae (Hymenoptera) egg parasitoids are released for the fall armyworm Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) management, and weeds are controlled mainly with glyphosate in corn Zea mays L. (Poales: Poaceae) crops. A glyphosate-based herbicide was sprayed at 13.94 L ha(-1) on eggs of the worldwide used alternative host, the Mediterranean flour moth Anagasta kuehniella Zeller (Lepidoptera: Pyralidae) parasitized by 10 Trichogrammatidae species, in a free-choice test. Parasitism, female emergence and female-biased sex ratio of these parasitoids were evaluated. Parasitism by Trichogramma acacioi Brun, Moraes & Soares, Trichogramma bennetti Nagaraja & Nagarkatti, Trichogramma brasiliensis Ashmead, Trichogramma galloi Zucchi, and Trichogramma pretiosum Riley was lower with glyphosate. This herbicide reduced the Trichogrammatoidea annulata de Santis, T. bennetti, Trichogramma bruni Nagaraja, Trichogramma demoraesi Nagaraja, T. galloi, and T. pretiosum female emergence. Female-biased sex ratio of T. annulata, T. bennetti, T. bruni, T. galloi, and T. pretiosum was lower with glyphosate. Glyphosate did not reduce the Trichogramma soaresi Nagaraja parasitism and female emergence, and, therefore, the use of this species has potential to be compatible with glyphosate.
Keywords: Chalcidoidea; Diammonium salt; Parasitoid; Substituted glycine; Weed; Zea mays